Sesquiterpene Lactones as Promising Candidates for Cancer Therapy: Focus on Pancreatic Cancer - Laurella, Laura Cecilia (2022)
Pancreatic ductal adenocarcinoma (PDAC) is a highly aggressive disease which confers to patients a poor prognosis at short term. PDAC is the fourth leading cause of death among cancers in the Western world. The rate of new cases of pancreatic cancer (incidence) is 10 per 100,000 but present a 5-year survival of less than 10%, highlighting the poor prognosis of this pathology. Fur-thermore, 90% of advanced PDAC tumor present KRAS mutations impacting in several oncogenic signaling pathways, many of them associated with cell proliferation and tumor progression. Different combinations of chemotherapeutic agents have been tested over the years without an improve-ment of significance in its treatment. PDAC remains as one the more challenging biomedical topics thus far. The lack of a proper early diagnosis, the notable mortality statistics and the poor outcome with the available therapies urge the entire scientific community to find novel approaches against PDAC with real improvements in patients’ survival and life quality. Natural compounds have played an important role in the process of discovery and development of new drugs. Among them, terpenoids, such as sesquiterpene lactones, stand out due to their biological activities and pharmacological potential as antitumor agents. In this review, we will describe the sesquiterpene lactones with in vitro and in vivo activity against pancreatic tumor cells. We will also discuss the mechanism of action of the compounds as well as the signaling pathways associated with their activity.